Following the Preclinical Data: Leveraging the Abscopal Effect More Efficaciously - Ngwa, Wilfred; Ouyang, Zi (Frontiers in Oncology, 2017)
Radiotherapy is employed in the treatment of over 50% of cancer patients. However, this therapy approach is limited to mainly treating localized disease. In 1953, Mole described the remarkable abscopal effect, whereby, localized radiotherapy of a patient’s primary tumor may engender regression of cancer at distant sites, which were not irradiated. Current consensus is that if the abscopal effect can be efficaciously leveraged, it would transform the field of radiation oncology, extending the use of radiotherapy to treatment of both localized and metastatic disease. A close examination of the literature on the abscopal effect proffers a disruptive new hypothesis for consideration in future clinical trials. This hypothesis is that generating a subcutaneous human tumor autograft as the primary tumor may be a more efficacious approach to prime the abscopal effect. Following the preclinical data, the merits and demerits of such an approach are examined in this article.